2013
DOI: 10.1190/geo2011-0521.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of fracture scattering

Abstract: We use a 2-D finite difference method to numerically calculate the seismic response of a single finite fracture in a homogeneous media. In our experiments, we use a point explosive source and ignore the free surface effect, so the fracture scattering wave field contains two parts: P-to-P scattering and P-to-S scattering. We vary the fracture compliance within a range considered appropriate for field observations, 10-12 m/Pa to 10-9 m/Pa, and investigate the variation of the scattering pattern of a single fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The Fresnel zone for the bottom reflections (red) is much wider than that for the top reflections (gray), indicating that the bottom reflections interfere with fracture-scattered waves that are generated from fractures spread over a broader region. Moreover, fracture scattering becomes stronger when it occurs further away from the midpoint because Pto-P fracture scattering generally becomes stronger when the incident angle with respect to the fracture plane increases (Fang et al, 2013a). Therefore, it is more difficult to analyze the AVAz of the bottom reflections.…”
Section: Randomly Distributed Fracturesmentioning
confidence: 99%
“…The Fresnel zone for the bottom reflections (red) is much wider than that for the top reflections (gray), indicating that the bottom reflections interfere with fracture-scattered waves that are generated from fractures spread over a broader region. Moreover, fracture scattering becomes stronger when it occurs further away from the midpoint because Pto-P fracture scattering generally becomes stronger when the incident angle with respect to the fracture plane increases (Fang et al, 2013a). Therefore, it is more difficult to analyze the AVAz of the bottom reflections.…”
Section: Randomly Distributed Fracturesmentioning
confidence: 99%
“…Fang et al (2013) found the same linear relationship between fracture scattering strength and fracture compliance when compliance is less than 10 -10 m/Pa, and they argued that the departure of this linear relationship at large compliance is due to the breakdown of the Born approximation. We here demonstrate that Z ξ <<η ξ is the necessary condition for the Born approximation (or weak scattering) to be valid for scattering from fractures.…”
Section: Relation Between Time Lapse Seismic Data and Fracture Complimentioning
confidence: 83%
“…The Z N /Z T ratio is strongly influenced by the way the fracture surfaces interact and it can be taken as an indicator representing the fracture saturation condition (Dubos-Sallée and Rasolofosaon, 2008;Fang et al, 2013). Both numerical simulations (Sayers et al, 2009;Gurevich et al, 2009) and laboratory measurements (Lubbe et al, 2008;Gurevich et al, 2009) suggest that Z N is generally smaller than Z T for reservoir fractures.…”
Section: Relative Strength Of Normal and Tangential Compliance Sensitmentioning
confidence: 99%
See 1 more Smart Citation
“…We first run a forward seismic simulation on the true compliance field (C T ) to generate the detailed wavefield [Schoenberg, 1980;Coates and Schoenberg, 1995;Fang et al, 2013]. The seismic response is affected by the underlying fracture mechanics parameters, such as fracture orientation, spacing, and compliance.…”
Section: Seismic Inversion and Error Modelingmentioning
confidence: 99%